PENERAPAN SANKSI PIDANA BAGI PELAKU EKSPLOITASI ANAK SEBAGAI PENGEMIS DI KOTA PEKANBARU - Septavio Thoyyiba Ridwan; Mukhlis R; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Children are both a mandate and a gift from God Almighty, who must always be guarded because they are inherent in their dignity and human rights which must be upheld. Children's rights are part of human rights contained in the 1945 Constitution of the Republic of Indonesia Articles 28A to 28J, the United Nations Convention on the Rights of the Child, Article 16 and Law of the Republic of Indonesia Number 35 of 2014 concerning Amendments. On Law Number 23 of 2002, concerning Child Protection in Article 4 to Article 19 concerning Children's Rights. The main problem in this research is how to apply criminal sanctions for child exploitation as beggars in Pekanbaru City, what are the obstacles in overcoming child exploitation as beggars in Pekanabru City and efforts to deal with obstacles for child exploitation actors as beggars in Pekanbaru City. The method used in this research is to use observational research by means of a survey, namely conducting research directly to the research location using data collection tools in the form of interviews. Meanwhile, when viewed from its nature, this research is descriptive, which means that it describes the facts studied about the factors of child exploitation crimes as beggars in Pekanbaru City and how are the efforts to tackle the crime of child exploitation as beggars in Pekanbaru City and what are the obstacles in overcoming child exploitation actors. as a beggar in Pekanbaru City.The result of this research is that the application of sanctions for child exploitation actors as beggars in Pekanbaru City has never or has not been brought forward to the investigation and investigation stage by the Police, because the application of criminal sanctions for exploitation actors must be first reported to the Police that children who experience losses due to this exploitation by parents or by irresponsible people. There are obstacles experienced by related agencies and the police in implementing sanctions, namely the Law which does not explain the limitations that can be said to be a criminal act of child exploitation. Efforts are made to overcome obstacles in implementing criminal sanctions, namely the need for socialization to all elements of society and individuals regarding the problem of child exploitation.Keywords: Application of Sanctions - Child Crime - Child Exploitation - Beggars